In vivo tracking and immunological properties of pulsed porcine monocyte-derived dendritic cells. Issue 2 (February 2015) - Crisci, Elisa; Fraile, Lorenzo; Novellas, Rosa; Espada, Yvonne; Cabezón, Raquel; Martínez, Jorge; Cordoba, Lorena; Bárcena, Juan; Benitez-Ribas, Daniel; Montoya, María
Highlights Human or pig dendritic cells pulsed with superparamagnetic iron oxide particles did not alter their phenotypic and functional properties in vitro in the experimental conditions tested in this work. After subcutaneous inoculation in pigs, porcine SPIO-MoDC migration to regional lymph nodes was detected by MRI and confirmed by Perls staining of draining lymph nodes. Only one dose of virus-like particles-pulsed MoDCs in pigs was able to induce specific local and systemic responses. This proof-of-principle study shows the potential of using pigs as a suitable animal model to test DC trafficking with the aim of improving cellular therapies.